2015
DOI: 10.4314/ahs.v15i2.47
|View full text |Cite
|
Sign up to set email alerts
|

Medical ethics in sub-Sahara Africa: closing the gaps.

Abstract: AbstractsBackground: Health care providers are expected to have the skills and knowledge relevant to their field and should also be familiar with the ethical and legal expectations that arise out of the standard practices. Objectives: To elucidate the practice of the health care providers in relation to healthcare ethics in Nigeria. Methods: A self-administered structured questionnaire was devised and distributed to staff of two tertiary health care facilities in Northern Nigeria. The questionnaire comprised o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…In addition, the qualitative findings of this study indicated gaps in practice of code of ethics among medical doctors. Our finding is in line with studies conducted in Pakistan and Nigeria [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the qualitative findings of this study indicated gaps in practice of code of ethics among medical doctors. Our finding is in line with studies conducted in Pakistan and Nigeria [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…The result of a cross-sectional descriptive study conducted in Lahore, Pakistan among medical doctors in a tertiary care teaching hospital indicated that medical doctors had poor practice of Pakistan Medical and Dental Council code of ethics [ 16 ]. Another study conducted through self-administered structured questionnaire in Nigeria identified gaps in practice of code of ethics among medical doctors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Monsudi et al and Imran et al argued that different intensity of professional training creates the difference in opinions among health staffs [30, 31]. Medical graduates receive hardly ten hours of lectures on medical ethics during their 5 years of medical degree, similarly, nurses receive limited orientation during their 3 years of training in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…It also extends to the consequences of wrong misdoings. The application of values and moral to human activities also constitute ethics [9]. The conduct of right and wrong are both related to ethics and morals.…”
Section: Overview Of Ethicsmentioning
confidence: 99%